PENANAMAN NILAI-NILAI KARAKTER RELIGIUS MELALUI KEGIATAN PEMBIASAAN DI MTS MA’ARIF DARUL AFKAR - Widianto, Suheri; Keivin (Darajat: Jurnal Pendidikan Agama Islam, 2025)
The decline of student morality and the increasing behavioral issues among youth present serious challenges in today’s educational landscape. To address this, religious character education must be instilled from an early age, particularly through habituation activities in the school environment. This study explores the implementation of religious character values including worship, jihad (struggle and perseverance), trustworthiness and sincerity, moral conduct and discipline, as well as exemplary behavior through habituation practices, particularly khitobah (religious speech), at MTs Ma’arif Darul Afkar Sendangharjo, Brondong, Lamongan. Employing a qualitative case study approach, data were collected through observation, interviews, and documentation involving school principals, teachers, and students. The findings reveal that khitobah is an effective medium for instilling religious values and fostering students' character and confidence. Key supporting factors include teacher role modeling and parental involvement. However, obstacles such as inadequate facilities, students’ low awareness, and negative influences from social and digital environments hinder the process. This article recommends improving infrastructure, strengthening school-parent collaboration, and implementing strategies to counter external influences so that religious habituation programs can be sustained and optimized.